Pengaruh Kepemilikan Institusional, Profitabilitas, dan Struktur Modal Terhadap Nilai Perusahaan - Wardoyo, Dwi Urip; Fauziah, Hera Dini (Politeknik Ganesha Medan, 2024)
Firm valuation reflects investors' assessment of a company's performance prospects in relation to its stock price. A higher firm valuation indicates increased prosperity for shareholders and signifies a company's attractiveness to investors. This research aims to conduct a thorough analysis of how institutional ownership, profitability, and capital structure affect the valuation of companies. The research specifically targets businesses within the property and real estate sector that are listed on the Indonesia Stock Exchange from 2017 to 2022. Employing a quantitative approach, the study employs purposive sampling to select a sample of 15 companies, resulting in a total of 90 observations. Data analysis is conducted using panel data regression, facilitated by Eviews 12 software. The research findings reveal that, when considered collectively, institutional ownership, profitability, and capital structure variables jointly contribute to influencing firm valuation. However, the outcomes of individual variable testing indicate that profitability significantly impacts firm valuation, whereas institutional ownership and capital structure do not exhibit a substantial influence on firm valuation.